A Critical Literature Analysis of Library and User Privacy - Noh, Younghee (International Journal of Knowledge Content Development & Technology, 2017)
This research aims at identifying through literature analysis the extent of past research related to the protection of personal information and privacy of library users. This study was conducted in 3 stages of literature analysis suggested by other researchers, including Powell (2005). First, I found and collected literature related to personal information and library user privacy. Second, I reviewed the collected literature and identified detailed subjects and core concepts. Third, I analyzed the core subjects, main discussion points, and related examples shown in those papers divided into 7 subgroups. I examine library privacy from various angles through literature analysis, and the results of this paper would be useful for establishing library privacy policies and developing guidelines for librarians. URL: http://ijkcdt.net/xml/10972/10972.pdf